PROCUREMENT IN MANUFACTURING ORGANISATION: PORTFOLIO AND THE USE OF THE INTERNET - I Nyoman Pujawan (Institute of Research and Community Outreach - Petra Christian University, 2003)
Procurement function in manufacturing organisations has played significantly more critical roles nowadays than in the past. The contribution of procurement function is much determined by how well the procurement management system is designed. A critical aspect of managing procurement function in order to optimise its contribution to the organisation is procurement portfolio, i.e., categorisation of items and then differentiation of procurement focus for different categories. This paper will discuss procurement portfolio as a basis for procurement manager to optimise the contribution of his/her function in supporting the organisation's objectives. The role of electronic procurement in each category of the portfolio will also be discussed.